Syringomyelia and Craniocervical Junction Abnormalities in Chihuahuas. (11th September 2017) - Kiviranta, A.‐M.; Rusbridge, C.; Laitinen‐Vapaavuori, O.; Hielm‐Björkman, A.; Lappalainen, A.K.; Knowler, S.P.; Jokinen, T.S.
Abstract : Background: Chiari‐like malformation (CM) and syringomyelia (SM) are widely reported in Cavalier King Charles Spaniels and Griffon Bruxellois dogs. Increasing evidence indicates that CM and SM also occur in other small and toy breed dogs, such as Chihuahuas. Objectives: To describe the presence of SM and craniocervical junction (CCJ) abnormalities in Chihuahuas and to evaluate the possible association of CCJ abnormalities with SM. To describe CM/SM‐related clinical signs and neurologic deficits and to investigate the association of CM/SM‐related clinical signs with signalment, SM, or CCJ abnormalities. Animals: Fifty‐three client‐owned Chihuahuas. Methods: Prospective study. Questionnaire analyses and physical and neurologic examinations were obtained before magnetic resonance and computed tomography imaging. Images were evaluated for the presence of SM, CM, and atlantooccipital overlapping. Additionally, medullary kinking, dorsal spinal cord compression, and their sum indices were calculated. Results: Scratching was the most common CM/SM‐related clinical sign and decreased postural reaction the most common neurologic deficit in 73 and 87% of dogs, respectively. Chiari‐like malformation and SM were present in 100 and 38% of dogs, respectively. Syringomyelia was associated with the presence of CM/SM‐related clinical signs ( P  = 0.034), and medullary kinking and sum indices were higher in dogs with clinical signs ( P  = 0.016 and P  = 0.007, respectively). Conclusions and Clinical Importance: Syringomyelia and CCJ abnormalities are prevalent in Chihuahuas. Syringomyelia was an important factor for the presence of CM/SM‐related clinical signs, but many dogs suffered from similar clinical signs without being affected by SM, highlighting the clinical importance of CCJ abnormalities in Chihuahuas.